Pemberdayaan Orang Tua Melalui Ecoprint Sebagai Media Edukasi Kreatif Untuk Anak Cinta Lingkungan - Nova Irawati; Mukhammad Wahyudi; Muhammad Fajrul Islam (LP3M IAIFA Kediri, 2025)
This community engagement program addresses the issue of limited parental involvement in nurturing children’s creativity and environmental awareness in early childhood settings. Many parents tend to focus on academic outcomes rather than process-oriented learning, which restricts opportunities for children to explore, experiment, and develop creative thinking. The focus of this program is to strengthen the role of parents as primary facilitators in fostering creativity and ecological sensitivity through an ecoprint-based learning activity. The program aims to: (1) enhance parents’ practical skills and understanding of creativity-oriented parenting; (2) cultivate children’s creativity and fine motor development through hands-on ecoprint activities; and (3) build meaningful collaborative interactions between parents and children. The method employed is the “Parent-as-Facilitator” model combined with a learning by doing approach grounded in local flora wisdom. Strategies include capacity building workshops, mindset transformation sessions, activity-based engagement, and guided simulations of effective parenting communication and emotional regulation. The results of the community engagement show significant improvements in three aspects: (1) parents demonstrated greater competence in ecoprint techniques and adopted more supportive, process-oriented parenting behaviors; (2) children exhibited increased creativity, environmental awareness, and fine motor skills; and (3) family interactions became more positive through increased quality time and shared learning experiences. Overall, this program demonstrates that ecoprint can serve as an effective medium for integrating creativity development and environmental education within the family context.